Potential Analysis of Rooftop Solar Power Plant Development Using PLN Mobile Application for Village Office Buildings in Lenek District, East Lombok, Indonesia - Muji Juherwin; Fahmi Abdullah; Yoga Dwi Hermawan; Moh Budi Shodikin (Journal of Renewable Energy, Electrical, and Computer Engineering, 2024)
This study evaluates the potential for rooftop solar photovoltaic (PV) installations on village office buildings in the Lenek District, East Lombok, Indonesia, using the PLN Mobile application. The primary objectives are to assess the potential installed capacity of rooftop solar PV systems, estimate the economic and environmental impacts of their installation, and evaluate the performance of the PLN Mobile application in simulating solar PV systems. The findings reveal that the application provided generalized recommendations, with suggested capacities of 0.6 kWp and 1.32 kWp, despite variations in electricity consumption, roof orientation, and other structural characteristics. Estimated installation costs range from Rp10,452,380 to Rp26,130,952, with potential monthly savings between Rp103,464 and Rp227,620, and a uniform reduction in carbon emissions of 0.285 kg CO2 per month. While the PLN Mobile application offers valuable preliminary insights, it lacks the necessary specificity to deliver precise assessments, leading to a potential mismatch between recommendations and the actual energy needs and structural conditions of the village offices. As a result, the study concludes that more customized evaluation methods are required to optimize the installation and performance of rooftop solar PV systems in village offices.